Potency of Combination of Palm Kernel Meal and Katuk Leaf Powder to Improve the Production Performance of Peranakan Etawa (PE) Goat: Toward a Strategy for Quality Control of Meat Using "CGE" Concept. (2015) - Ferasyi, Teuku Reza; Akmal, Muslim; Hamdani, B.; Razali,; Azhari,; Wahyuni, Sri; Amiruddin,; Anwar,; Pamungkas, Fitra Aji; Nasution, Saddat; Barus, Rina Aulia
Abstract: This research was aimed to study the potency of suplementation of a combination of palm kernel meal and katuk leaf powder (Sauropus androgynus L. Merr) to the production performance in PE goat. The final target of this study is to develop a strategy for quality control of meat using a "clean, green, and ethical" (CGE) concept of technology. This study were used 20 male PE goat at aged of+ 1.5 years and weight of 15-20 kg. The result showed that the suplementation of BISKAT was induced a higher level of testosterone in male PE goat. In conclusion, testosterone levels of PE goat tends to increase after given a combination of palm kernel meal and katuk leaf powder. Therefore, the technique used in this research might direct us to to develop a strategy for quality control of meat product in livestock using a "clean, green, and ethical" (CGE) concept of technology in the future.